2015
DOI: 10.1002/pds.3816
|View full text |Cite
|
Sign up to set email alerts
|

Hip/femur fractures associated with the use of benzodiazepines (anxiolytics, hypnotics and related drugs): a methodological approach to assess consistencies across databases from the PROTECT‐EU project

Abstract: Background Results from observational studies may be inconsistent because of variations in methodological and clinical factors that may be intrinsically related to the database (DB) where the study is performed. Objectives The objectives of this paper were to evaluate the impact of applying a common study protocol to study benzodiazepines (BZDs) (anxiolytics, hypnotics, and related drugs) and the risk of hip/femur fracture (HFF) across three European primary care DBs and to investigate any resulting discrepanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…Benzodiazepines confer their effects through their action on γ-amino-butyric acid (GABA) type A receptors in the central nervous system, which are molecular substrates for the regulation of vigilance, anxiety, muscle tension, epileptogenic activity, and memory functions. 38 Because of their psychotropic action, benzodiazepines have been associated with hypnotic related side effects such as daytime sleepiness, impairment of psychomotor and cognitive functioning, increased risk of motor vehicle collisions, and increased risk of falls and fractures, [39][40][41][42] in particular among older patients, 31 and with possible greater risks for benzodiazepines with a longer half life. 32 33 Benzodiazepines have also been associated with an increased risk for development of dependence and misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines confer their effects through their action on γ-amino-butyric acid (GABA) type A receptors in the central nervous system, which are molecular substrates for the regulation of vigilance, anxiety, muscle tension, epileptogenic activity, and memory functions. 38 Because of their psychotropic action, benzodiazepines have been associated with hypnotic related side effects such as daytime sleepiness, impairment of psychomotor and cognitive functioning, increased risk of motor vehicle collisions, and increased risk of falls and fractures, [39][40][41][42] in particular among older patients, 31 and with possible greater risks for benzodiazepines with a longer half life. 32 33 Benzodiazepines have also been associated with an increased risk for development of dependence and misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Four case–control or cohort studies have assessed the risk of hip or hip/femur fracture as a result of concurrent use of psychoactive medicines defined in terms of current exposure [710]. An increased risk of hip or hip/femur fracture was found for current use of opioids with psychotropic medicines, current use of anxiolytics with hypnotics, and current use of benzodiazepines or zolpidem with potentially interacting medicines identified in drug information sources [7, 8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of hip or hip/femur fracture was found for current use of opioids with psychotropic medicines, current use of anxiolytics with hypnotics, and current use of benzodiazepines or zolpidem with potentially interacting medicines identified in drug information sources [7, 8, 10]. For each combination of a benzodiazepine or zolpidem with interacting medicines, an assessment of additive interaction found that the risk estimate as a result of concurrent exposure was similar to the sum of the risk estimates due to individual exposures [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no relevant impact of considering such confounders on LABA-associated AMI risk estimates was found in other studies suggesting confounding by, e.g., lifestyle factors as already captured to a large extent by routinely collected confounders [37]. Similarly, for another drug-AE pair (benzodiazepines and hip/femur fractures) examined within the PROTECT project, consideration of additional lifestyle factors (e.g., alcohol, smoking) as part of a sensitivity analysis had no relevant impact on risk estimates in CPRD GOLD database [38]. However, we did include exposure information on several drugs prescribed for exacerbations (e.g., oral corticosteroids) as confounders in the sensitivity analysis, acting as a proxy for disease severity.…”
Section: Study Strengths and Limitationsmentioning
confidence: 89%